Priming and de‐priming of neutrophil responses in vitro and in vivo. (5th July 2018) - Vogt, Katja L.; Summers, Charlotte; Chilvers, Edwin R.; Condliffe, Alison M.
Abstract: The activation status of neutrophils can cycle from basal through primed to fully activated ("green‐amber‐red"), and at least in vitro, primed cells can spontaneously revert to a near basal phenotype. This broad range of neutrophil responsiveness confers extensive functional flexibility, allowing neutrophils to respond rapidly and appropriately to varied and evolving threats throughout the body. Primed and activated cells display dramatically enhanced bactericidal capacity (including augmented respiratory burst activity, degranulation and longevity), but this enhancement also confers the capacity for significant unintended tissue injury. Neutrophil priming and its consequences have been associated with adverse outcomes in a range of disease states, hence understanding the signalling processes that regulate the transition between basal and primed states (and back again) may offer new opportunities for therapeutic intervention in pathological settings. A wide array of host‐ and pathogen‐derived molecules is able to modulate the functional status of these versatile cells. Reflecting this extensive repertoire of potential mediators, priming can be established by a range of signalling pathways (including mitogen‐activated protein kinases, phosphoinositide 3‐kinases, phospholipase D and calcium transients) and intracellular processes (including endocytosis, vesicle trafficking and the engagement of adhesion molecules). The signalling pathways engaged, and the exact cellular phenotype that results, vary according to the priming agent(s) to which the neutrophil is exposed and the precise environmental context. Herein we describe the signals that establish priming (in particular for enhanced respiratory burst, degranulation and prolonged lifespan) and describe the recently recognised process of de‐priming, correlating in vitro observations with in vivo significance.